Mind over matter: Deducing heatstroke pathology - Noakes, T. D. (The Physician and Sportsmedicine, 2005)
Heat injury has been much in the news of late, with the American College of Sports Medicine releasing guidelines in August on youth football and heat stress, and a recent study detailing 5,246 US Army soldiers' hospitalization and 37 deaths due to "heat illness."1 It's time to take a critical, logical look at some of the underlying causes, and what, indeed, would constitute proper preventive measures.